Carbonic anhydrase IX immunohistochemistry has potential to predict renal cell carcinoma outcomes: A systematic review and meta-analyses - Samberkar, Snehlata Prashant; Rajandram, Retnagowri; Mun, Kein Seong; Samberkar, Prashant Naresh; Danaee, Mahmoud; Zulkafli, Intan Suhana (College of Pathologists, Academy of Medicine Malaysia, 2019)
INTRODUCTION: Tissue biomarker carbonic anhydrase IX (CAIX) is purported to have prognostic value for renal cell carcinoma (RCC) but contradicting findings from previous studies have also been documented. This study aims to perform a systematic review and meta-analysis on the role of CAIX in RCC disease progression. MATERIALS AND METHODS: Following the preferred reporting items for systematic review and meta-analysis (PRISMA) guidelines, online searches of multiple databases were performed to retrieve articles from their inception until December 2017. Inclusion criteria included all English-based original articles of immunohistochemistry (IHC) studies investigating CAIX expression in human RCC tissue. Four articles were finally selected for meta-analysis with a total of 1964 patients. Standard meta-analysis methods were applied to evaluate the role of CAIX in RCC prognosis. The relative risk (RR) and its 95% confidence interval (CI) were recorded for the association between biomarker and prognosis, and data were analysed using MedCalc statistical software. RESULTS: The meta-analysis showed that high CAIX expression was associated with low tumour stage (RR 0.90%, 95% CI 0.849-0.969, p= 0.004), low tumour grade (RR 0.835%, 95% CI 0.732-0.983, p= 0.028), absence of nodal involvement (RR 0.814%, 95% CI 0.712-0.931, p= 0.003) and better ECOS-PS index (RR 0.888%, 95% CI 0.818-0.969, p= 0.007). The high tissue CAIX expression in RCC is hence an indication of an early malignancy with a potential to predict favourable disease progression and outcome. CONCLUSION: The measurement of this marker may be beneficial to determine the course of the illness. It is hoped that CAIX can be developed as a specific tissue biomarker for RCC in the near future.